HUBUNGAN POWER OTOT TUNGKAI DAN KOORDINASI MATA DAN TANGAN DENGAN KETEPATAN SMASH BOLAVOLI ATLET SEKOLAH BOLAVOLI LANGSAT PERMAI - Wahyu Setiono; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Based on observations by researchers in the field, it shows that from the volleyball competitions that were followed, the Volleyball athlete Langsat Permai had won, but this did not last long. This is because the smash accuracy of the Langsat Permai Volleyball School athletes is not very good. It is seen when making an easy smash on the block with the opponent, then the ball is not on target or the ball is out. Apart from that the smashes made by athletes often hit the net, are easily taken by opponents and so on. The purpose of this study was to prove the relationship between leg muscle power and eye and hand coordination with the accuracy of volleyball smashes for Langsat Permai Volleyball School athletes. The population in this study were all volleyball athletes at Langsat Permai Volleyball School who took part in the volleyball training, totaling 12. Given the small population that will be sampled as well as the players who participate in the training. Thus the sample was taken by 12 volleyball players. The instrument in this study used the leg muscle power test using a vertical power jump test measuring instrument. Eye and hand coordination using a catch-ball test. Volleyball smash accuracy test by measuring the results of the smash accuracy using a target box that contains numbers made in the field according to the level of difficulty. The data obtained were analyzed using simple and multiple correlation. Based on the results of the research that the author has described in the previous chapter, it can be concluded, From the results obtained, leg muscle power has a significant relationship with Smash accuracy in Volleyball Volleyball athletes Langsat Permai School, where rcount (0.684)> household (0.602). From the results obtained, eye and hand coordination has no relationship with the accuracy of Smash in Volleyball Volleyball athletes at Langsat Permai Volleyball School, where rcount (0.083) <rtab (0.602). There is a joint relationship between leg muscle power and eye and hand coordination to the accuracy of Smash in Volleyball Volleyball athletes in Langsat Permai Volleyball School, where rcount (0.694)> rtab (0.602).Key Words: Leg Muscle Power, Hand and Eye Coordination, Smash Accuracy